2002
DOI: 10.1152/ajpheart.00257.2001
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate-induced cardiac apoptosis is mediated through CPT-1 but not influenced by glucose and insulin

Abstract: Kong, Jennifer Y., and Simon W. Rabkin. Palmitateinduced cardiac apoptosis is mediated through CPT-1 but not influenced by glucose and insulin. Am J Physiol Heart Circ Physiol 282: H717-H725, 2002; 10.1152/ajpheart.00257. 2001.-To test the hypothesis that regulation of palmitate metabolism, through carnitine palmitoyl transferase-1 (CPT-1) or through alterations of glycolysis, was involved in the pathway of palmitate-mediated cell death, cardiomyocytes were cultured from 7-day-old chick embryos. Palmitateindu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…This suggests that in the human heart or at least in the atrium, ceramide is not a major mediator of cardiomyocyte apoptosis associated with obesity and type 2 diabetes and that other factors play a dominant role in this process. It was shown that palmitate can induce cardiomyocyte apoptosis independently of ceramide via generation of reactive oxygen species resulting from increased cycling through mitochondrial ␤ -oxidation pathway ( 32,33 ). In addition, apoptosis of cardiomyocytes is activated by hyperglycemia through a mechanism involving excessive protein O-glycosylation ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that in the human heart or at least in the atrium, ceramide is not a major mediator of cardiomyocyte apoptosis associated with obesity and type 2 diabetes and that other factors play a dominant role in this process. It was shown that palmitate can induce cardiomyocyte apoptosis independently of ceramide via generation of reactive oxygen species resulting from increased cycling through mitochondrial ␤ -oxidation pathway ( 32,33 ). In addition, apoptosis of cardiomyocytes is activated by hyperglycemia through a mechanism involving excessive protein O-glycosylation ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, oxidation of glucose to CO2 yields 0 mol H ϩ /mol glucose (15,37). Therefore, the overall rate of H ϩ production derived from glucose utilization was determined as follows (3,21,24):…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of the different proton stoichiometry of glucose fermentation compared with oxidation (15,37), this protective effect has been suggested to be related to a reduction in net proton production from glucose catabolism (2,3,21,24,25,45). Such a reduction was shown to favor the recovery of intracellular pH, which could limit calcium overload by way of successive trans-sarcolemmal H ϩ /Na ϩ and Na ϩ /Ca 2ϩ exchange and therefore reduce the energetic cost associated with the maintenance of ion homeostasis (21,24). This would in turn lead to improved postischemic contractile function and efficiency (see Refs.…”
Section: Potential Role Of Altered Glucose Catabolism In Cardioprotecmentioning
confidence: 99%
“…These hearts display evidence of myocyte dropout due to activation of apoptotic pathways. Indeed, direct treatment with saturated long-chain FAs has been shown to trigger apoptosis in cardiac myocytes as well as in other cell types in culture via mechanisms that may involve generation of reactive oxygen species (105)(106)(107). Collectively, observations in mice and humans indicate that severe reduction in mitochondrial FAO capacity sets the stage for cardiac lipotoxic effects related to lipid intermediates that accumulate in the context of impaired catabolism.…”
Section: Do Derangements In Mitochondrial Energy Metabolism Cause Heamentioning
confidence: 99%